Report on Conservation of Water Resources and Control of Water Pollution - Planning Commission, Government of India (Planning Commission, Government of India, 1963)
While the country's water resources are yet to be fully harnessed the situation with regard to available supply is aggravated by an increasing degree of pollution in almost all the river courses. With the rapid industrialization, growing urbanization and increase in population in many parts of the country there is an indiscriminate discharge of untreated or inadequately treated community and industrial wastes into the water courses. Communities and industries have to spend more in treating. polluted waters to make them fit for their use.
Committee on Plan Projects (Buildings Projects Team)
Committee on Plan Projects (Buildings Projects Team)
Keywords: Water resources and water supply